Description of Chistyakovella insolita gen. nov., sp. nov., and redescription of the type species of Diplobodes, D. kanekoi Aoki, 1958 (Acari: Oribatida: Carabodidae) - Ermilov, Sergey G.; Aoki, Jun-Ichi; Anichkin, Alexander E. (Zootaxa, 2013)
A new oribatid mite genus, Chistyakovella gen. nov. (Carabodidae), with type species C. insolita sp. nov., is proposed and described from Southern Vietnam. It is clearly distinguished from other carabodid genera by the lamellae, which are touching medially. The new genus is most similar morphologically to Gibbicepheus Balogh, 1958 and Diplobodes Aoki, 1958, however it can be clearly distinguished from both genera by the position of interlamellar setae and the number of notogastral setae on the humeral regions of the notogaster. The type species of the genus Diplobodes, D. kanekoi Aoki, 1958, is redescribed from Japan. An identification key to known species of Diplobodes is presented.